Briquetting of fine size asphaltite without binder - Atesok, G; Özer, M; Burat, F; Önal, G; Gülen, J (TAYLOR & FRANCIS INC, 2005)
In this study, the effects of particle size, moisture, briquetting pressure, and preheating temperature were investigated on briquetting without binder of Sirnak Asphaltite, having a particle size of 20 mm, 46.22% ash, 5.83% total sulphur content, and 4900 kcal/kg kg calorific value. At the end of the briquetting experiments; mechanical strength values of briquettes produced in optimum conditions ( particle size, - 1 mm; moisture, 3.6%; pressing value, 4 t/cm(2); amount of lime, 12%) have the properties of first-class briquettes according to Turkish standards. The mechanical strength values of produced briquettes were affected positively in optimum conditions with preheating to 80 degrees C. In combustion experiments using an upper burning stove, the combustion efficiency of briquettes, which contain 50.54% ash, 16.08% fixed carbon, 33.38% volatile matter, and 4.80% total sulphur have been calculated as 60%. During the combustion, sulphur content in smoke gas and particle emissions were determined as 2.34% and 3 mg/m(3), respectively.
Keywords: asphaltite; briquette; binder; mechanical strength; domestic fuel; Metallurgy & Metallurgical Engineering; Mining & Mineral Processing